Lyman J. Gage correspondence - Gage, Lyman J. (Lyman Judson), 1836-1927.
Correspondence chiefly documenting Gage's service as U.S. secretary of the treasury in the William McKinley and Theodore Roosevelt administrations and subsequently as president of the United States Trust Company of New York. Subjects include fiscal matters such as the financing of the war with Spain. Correspondents include R.A. Alger, George B. Cortelyou, Ralph M. Easley, Marcus Alonzo Hanna, Orville Peckham, James B. Pond, Elihu Root, Charles Emory Scott, and others.
Banker and public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alger, R. A. -- 1836-1907 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Easley, Ralph M. -- 1858- -- Correspondence; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; McKinley, William, -- 1843-1901.; Peckham, Orville, -- 1846-1927 -- Correspondence; Pond, James B. -- 1838-1903 -- Correspondence; Roosevelt, Theodore, -- 1858-1919.; Root, Elihu, -- 1845-1937 -- Correspondence; Scott, Charles Emory -- Correspondence; United States Trust Company of New York; Banks and banking -- New York (State) -- New York; Finance, Public -- United States; Spanish-American War, 1898 -- Finance; Bankers; Cabinet officers; Public officials